2019
DOI: 10.3389/fmicb.2019.02777
|View full text |Cite
|
Sign up to set email alerts
|

Is Meropenem as a Monotherapy Truly Incompetent for Meropenem-Nonsusceptible Bacterial Strains? A Pharmacokinetic/Pharmacodynamic Modeling With Monte Carlo Simulation

Abstract: Infections due to meropenem-nonsusceptible bacterial strains (MNBSs) with meropenem minimum inhibitory concentrations (MICs) ≥ 16 mg/L have become an urgent problem. Currently, the optimal treatment strategy for these cases remains uncertain due to some limitations of currently available mono- and combination therapy regimens. Meropenem monotherapy using a high dose of 2 g every 8 h (q 8 h) and a 3-h traditional simple prolonged-infusion (TSPI) has proven to be helpful for the treatment of infections due to MN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 69 publications
(81 reference statements)
2
17
0
Order By: Relevance
“…Drawing on our previous results on meropenem against highly resistant bacteria (Song et al, 2019) and the hypothesis stated by Pea et al regarding the usefulness of continuous infusion for the treatment of borderline-susceptible pathogens (Pea and Viale, 2008), joint infusion mode with loading-rate rapid infusion (LRRI) and low-rate continuous infusion (LRCI) was speculated to be optimal and capable of yielding sufficient drug exposure for isolates with high MICs. Thus, the novel dosing strategy FIGURE 1 | Concentration-time profiles for TIII and OTSI.…”
Section: Design Of a Novel Dosing Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…Drawing on our previous results on meropenem against highly resistant bacteria (Song et al, 2019) and the hypothesis stated by Pea et al regarding the usefulness of continuous infusion for the treatment of borderline-susceptible pathogens (Pea and Viale, 2008), joint infusion mode with loading-rate rapid infusion (LRRI) and low-rate continuous infusion (LRCI) was speculated to be optimal and capable of yielding sufficient drug exposure for isolates with high MICs. Thus, the novel dosing strategy FIGURE 1 | Concentration-time profiles for TIII and OTSI.…”
Section: Design Of a Novel Dosing Strategymentioning
confidence: 97%
“…If the dilemma without better options in the presence of BS H−VAN−M infections can be broken through by optimizing the administration of the available drugs which have a currently reduced competency for such infections, it must be helpful for clinicians to treat such infections. Surprisingly, studies have shown that meropenem, with administration optimization, can still achieve sufficient PK/PD exposure against highly resistant bacterial isolates (Song et al, 2019), which has aroused substantial interest in exploring the "new usage for old drugs" to improve and maximize the performance of VAN against BS H−VAN−M infections. If successful, this exploration will have important significance in clinic, especially considering the rapid progress against the MIC creep phenomenon, delays in the development of new alternatives, and lack of better treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Based on PK/PD modeling with Monte Carlo simulations, optimized prolonged infusion treatment regimens to overcome resistance have been proposed for a variety of time-dependent antimicrobials whose efficacy is best predicted by the time that the antibiotic’s concentration is above the MIC (% T > MIC, or % f T > MIC considering the free, unbound drug concentration). For example, two-step administration of meropenem (1.5 g administered intravenously over 5 min followed by a 6 h infusion of 0.5 g, repeated every 8 h) can achieve a > 90% probability of target attainment for carbapenem-resistant isolates with MIC up to 128 mg/L (considering a target 50% f T > MIC), or up to 32 mg/L (considering a higher target of 50% f T > 5 × MIC) [ 188 ]. Regarding ceftolozane/tazobactam, an extended (4–5 h) infusion may perform better compared to shorter or longer infusions, especially in patients with augmented renal clearance, and has been proposed to achieve target attainment (40% fT > MIC) for P. aeruginosa strains with MIC up to 32 mg/dl [ 189 ].…”
Section: Pk/pd Considerations and Dosing Strategies For Overcoming Rementioning
confidence: 99%
“…The rationale of this combination is that ertapenem due to its higher affinity with the carbapenemase enzyme acts as a suicide inhibitor, allowing higher levels of the second carbapenem (typically meropenem or doripenem) [69][70][71][72]. Optimized two-step administration (intravenous bolus followed by prolonged infusion) of meropenem has also been proposed for carbapenem-resistant isolates with MIC up to 32mg/L (and potentially up to 128mg/L) [73], but clinical data are lacking.…”
Section: Brief Overview Of the Mechanisms Of Resistance To Carbapenemsmentioning
confidence: 99%
“…High-dose amikacin (25-50mg/kg/day) may also be an option for CACT-resistant P. aeruginosa with borderline resistance to amikacin (MIC=16mg/dl) [114]. Optimized two-step administration of meropenem (as described above for K. pneumoniae) may also be an option but clinical data are lacking [73]. Finally, various synergistic combinations (e.g.…”
Section: Options For Cact-resistant P Aeruginosamentioning
confidence: 99%